Qualitative interviewing - Brinkmann, Svend (Oxford Oxford University Press, 2013)
Qualitative interviewing has today become one of the most common research methods across the human and social sciences, but it is an approach that comes in different guises. This book will help its readers write, represent, understand, and critique qualitative interview research in its many forms as currently practiced. The book begins with a theoretically informed introduction to qualitative interviewing by presenting a variegated landscape of how conversations have been used for knowledge-producing purposes. Particular attention is paid to the complementary positions of experience-focused interviewing (phenomenological positions) and language-focused interviewing (discourse-oriented positions), which focus on interview talk as reports (of the experiences of interviewees) and accounts (occasioned by the situation of interviewing), respectively.
Includes bibliographical references (pages 159-168) and index.
Keywords: Interviewing; Interviewing in sociology; Qualitative research